Peace and Resistance in Nonwestern and Western Countries - Steinmetz, Carl H. D. (Advances in Social Sciences Research Journal, 2025)
This study explores the dynamic interplay between peace and resistance initiatives, comparing Western and non-Western frameworks to reveal how cultural, historical, and philosophical traditions shape their conceptualization and application. Drawing from critical peace studies, decolonial thought, and comparative political philosophy, the research examines whether resistance precedes peace, follows it, runs in parallel, or even undermines it—across diverse contexts. Western paradigms often define peace as the absence of conflict and resistance as a response to tyranny, framed through Enlightenment ideals of civil disobedience, individual rights, and liberal democracy. In contrast, non-Western perspectives emphasize holistic peace rooted in justice, spiritual balance, and relational harmony, while resistance is often embedded in collective survival, epistemic sovereignty, and cultural renewal. Through detailed analysis of both traditions—including inner resistance in Eastern philosophies, Indigenous struggles for land and cosmology, and Western theories from Locke to Foucault—the paper argues that resistance and peace are not antithetical but interdependent. Nonviolent resistance, spiritual defiance, and cultural resilience are shown to be essential forms of peacebuilding, particularly in non-Western contexts where structural violence and colonization persist. This rethinking of peace-resistance relations suggests that sustainable peace must engage with, rather than suppress, acts of resistance aimed at justice and dignity.